La desnaturalización de la acción de despido ineficaz por la falta de acuerdo entre las partes, en el proceso laboral. - Aguilar Heredia, Eleuterio Edulfo (2025)
Teenage pregnancy represents a considerable challenge for socioeconomic development in Ecuador, with important implications for public health and human capital development. The general objective of this research is to analyze the incidence of schooling level on teenage pregnancy in Ecuador in 2019, through descriptive analysis and discrete choice models at both the individual and provincial levels, in order to contribute with relevant information to facilitate the formulation of public policies focused on reducing teenage pregnancy and improving educational opportunities in different regions. The data were extracted from the National Institute of Statistics and Census (INEC) from the National Health and Nutrition Survey (ENSANUT, 2019) and the National Survey of Employment, Unemployment and Underemployment (ENEMDU, 2019), using descriptive statistical techniques and hierarchical discrete choice models. As the main findings, 15,8% of Ecuadorian adolescents experienced a pregnancy during 2019, with an educational gap of 1,2 years between teenagers with and without pregnancy. Each additional year of schooling reduces the probability of teenage pregnancy by 3,4%, with this effect being more evident at lower educational levels. At the provincial level, population and economic concentration increase the probability of teenage pregnancy by 59,2%. Disparities are notable, with higher incidence in rural areas and minority ethnic groups, demonstrating the urgency of territorially differentiated public policies that strengthen access to education, and sexual and reproductive health programs. Keywords: Human capital; Level of schooling; Multilevel analysis. Public policies; Teenage pregnancy; Territorial inequality;